APLIKASI CHATBOT UNTUK PENERIMAAN MAHASISWA BARU UNIVERSITAS INDO GLOBAL MANDIRI MENGGUNAKAN DEEP LEARNING - Desrika Heryati; Zulkifli; Ricky Maulana Fajri (Universitas Indo Global Mandiri, 2023)
Most prospective new students want to get fast and accurate information. Prospective new students certainly want to get a lot of information about the procedure for registering new students at each tertiary institution, especially Indo Global Mandiri University. Information on new student admissions at Indo Global Mandiri University only uses websites and social pages as general information. To overcome this problem, a new student acceptance chatbot application was created at Indo Global Mandiri University to provide information that can summarize well and display the information to users. To create this chatbot using the Python programming language using Deep learning. The deep learning algorithm model that is applied in making chatbots uses the Artificial Neural Network model. The application of the Artificial Neural Network model can recognize question patterns quickly and accurately so as to get an appropriate response. The model was then tested with 15 different conversations and successfully answered with a chatbot accuracy value of 86% and 13% error